Perception And Preference Towards Siddha Medicines During Covid-19 In Tamil Nadu (Journal of Pharmaceutical Negative Results, 2023)
The COVID-19 outbreak caused a huge loss of life, both for the victims and their families. It brought to a financial catastrophe that had unanticipatedly large proportions globally and ruined livelihoods. The Indian government has collaborated with the Ministry of Ayush to establish a number of policies and preventative actions to combat the COVID-19 epidemic. Patients have benefited from the use of these strategies in conquering the early stages of Corona virus infection. In light of COVID-19, the researcher is interested in learning how the general public in Tamil Nadu thinks about and favours Ayurvedic medicines. The researcher also wanted to know the respondents' preferences for the Ayurvedic medications they frequently used to treat different conditions. The results of the study were widely publicized throughout Tamil Nadu. The convenience sampling technique was used to gather the samples from the study area. The sample included 390 respondents. The research model was framed by the variables perception, usage, preference, and satisfaction. Four hypotheses were presented for this investigation. Primary data was acquired using a well-structured questionnaire. Variables pertaining to perception, usage, preference, and satisfaction were included in the questionnaire. This shows that consumption serves as a mediating variable in the relationship between consumer perception and desire for Ayurvedic medicines. Preference perception is significant at a level of 0.05. The research methodology and assumptions were tested and determined to be true, yet there is no significant relationship between utilisation and satisfaction.